Progressive wear prediction of C/C composite finger seal based on ALE adaptive meshing strategy. (May 2017) - Lu, Fei; Chen, Guoding; Su, Hua; Wang, Li'na; Zhang, Yanchao
Leakage clearance between the finger seal and the rotor is influenced by the seal wear, and a large leakage clearance may cause sealing failure. The aim of this study is to develop a predictive method to simulate the progressive wear of C/C composite finger seal. A finite element model is presented for the finger seal dynamic motion. A wear model is built by calculating the local wear rate for the nodes on finger foot bottom and by introducing an Arbitrary Lagrangian Eulerian adaptive meshing strategy. Progressive wear analysis is implemented by integrating the finger dynamic motion and the wear model. The results show that the contact pressure of finger seal is decreased and the leakage clearance is increased with operating time due to progressive wear. Compared to the case that the non-woven cloth is parallel to rotor surface (O1 ) and the case that the non-woven cloth is perpendicular to rotor surface but the laminated direction is perpendicular to sliding direction (O2 ), low leakage and low wear are obtained when the non-woven cloth is perpendicular to rotor surface and the laminated direction is the same as sliding direction (O3 ). In addition, the wear depth of finger foot and the leakage clearance between the finger seal and rotor are both increased with pressure differential and rotor speed.